Out of bounds : sports in the inner city - Smith, Stephen A. (Stephen Anthony), 1967-; Macmillan, Jackie; Jackson, Robert, 1963 November 22- (Noube Productions., 2015)
This Emmy Nominated documentary brings together for the first time some of the largest local and national names in sports. ESPN's Stephen A Smith, Jackie Macmillan, and Robert "Scoop" Jackson give their perspectives on the importance of athletes and finding success after sports. Basketball Division 1 standout Brian Rudolph (New Bedford), All American Matt King (Stoughton), All Conference Kharee Louis Jeune (Brockton), and others are chronicled about their life in the toughest parts of the city and how sports was their ticket out.